1976
DOI: 10.1172/jci108492
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between right duct lymph flow and extravascular lung water in dogs given alpha-naphthylthiourea.

Abstract: A B S T R A C T The relationship between right duct lymph flow and extravascular lung water was studied in 3 normal dogs and 15 dogs with pulmonary edema induced by a-naphthylthiourea (ANTU). Right Thus, in ANTU-induced pulmonary edema right duct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A third commonly used model of lung injury is that induced by α‐naphthylthiourea (ANTU), which produces marked pulmonary oedema and pleural effusions resulting from increased permeability changes in the lung microvasculature (Latta, 1947; Pine et al 1976). Morphological studies by light and electron microscopy indicated that the capillary endothelial cell is the primary cellular target of ANTU toxicity (Cunningham & Hurley, 1972; Meyrick et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…A third commonly used model of lung injury is that induced by α‐naphthylthiourea (ANTU), which produces marked pulmonary oedema and pleural effusions resulting from increased permeability changes in the lung microvasculature (Latta, 1947; Pine et al 1976). Morphological studies by light and electron microscopy indicated that the capillary endothelial cell is the primary cellular target of ANTU toxicity (Cunningham & Hurley, 1972; Meyrick et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…After development of pulmonary edema, the lymphatics may continue the normal function of conservation of plasma filtrate. In addition, they may function as conduits for removing accumulated extravascular fluid (Pine et al, 1976). We designed experiments to study the dynamics of transvascular fluid flux and lymph flow during and after development of pulmonary edema.…”
Section: The Dynamics Of the Lung Fluid Filtrationmentioning
confidence: 99%
“…Many factors promote pulmonary lymph flow, including the elevation of the left atrial pressure, increased bronchial arterial perfusion, hemodilution, increased cardiac output, and so on. In contrast, lymph flow may decline with the elevation of lymphatic outflow pressure; the effective resistance of the extrapulmonary part of the lymphatic system was larger than the resistance of the lymphatics in the lungs, and it may limit the maximal flow of lymph from edematous lungs [56][57][58][59][60][61][62][63][64][65][66] .…”
Section: Pulmonary Lymphatic Vessels and Lymph Flowmentioning
confidence: 99%